MENINGKATKAN EFISIENSI ADMINISTRASI DI KLINIK DOKTER UMUM MELALUI IMPLEMENTASI APLIKASI MEDICAL PRIVATE PRACTICE - Amirazanthi, Reynata; Hayati, Cucu (PUTRA JAWA PUBLISHER, 2023)
This research discusses improving administrative efficiency in general practitioner clinics through the implementation of the Medical Private Practice (MPP) application. Efficient administration is essential in running the operations of a GP clinic in order to provide optimal service to patients. However, administrative processes that are still carried out manually often cause challenges and obstacles in patient data management, scheduling, payment, and inventory management. The type of research used in implementing the MPP application is qualitative research with a case study approach. This research methodology allows data collection through observation, interviews, and documentation to understand the changes that occur after the implementation of the MPP application. The results showed that the use of the MPP application significantly improved administrative efficiency at the GP clinic. The benefits include better patient data management, efficient scheduling, easy payment, and more accurate inventory management. This has a positive impact on service quality, patient satisfaction, and overall clinic efficiency and productivity.